Analisa Metode Handover Pada Jaringan WiMAX - Murhaban Murhaban; Ahmad Ashari (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2016)
Handover method is used to keep the stabilization of connection. Its connected with the performance was caused the process canal traffic transfer automatically in mobile station (MS) that was used to communicate without cutting off the connection. The main factor of success in handover was quality of service to provide the difference level of service in arranging and giving the traffic priority in the network like voice over IP (VoIP) application or communication voice using internet network.             This research will analyse the achievement quality of service in the WiMax network standard 802.16e used hard handover and softhandover method with the VoIP application in mobile station.            Based on the testing that was carried out hard handover and soft handover method used  the application of voice over internet protocol in mobile station has obtained  value jitter 0.001 Ms – 0.31 ms, and delay 10.5 ms 39 ms this is proved that the influence of jitter and delay against handover with the VoIP application still in the tolerance stage that was permitted.  It is different with the output throughput 85 Bit/Sekon  - 550 Bit/Sekon that is too low and indicated that throughput is not sentitif against handover with the voice over  internet protocol application.